SUDDEN DEATH DURING LAPAROSCOPIC TUBAL LIGATION A CASE SERIES (Journal of Forensic Medicine & Toxicology, 2020)
Female sterilization or tubal ligation (TL) or tubectomy is the most accepted method of contraception in India. Laparoscopic tubal ligation is a safe effective and procedure of choice of majority of the surgeons. Though the incidences of complications are less in laproscopic TL but sudden unexpected deaths due to cardiac arrest also has been reported. Here the author present two cases, which were brought to the autopsy examination with history of sudden death during the laproscopic TL.
Keywords: Tubal ligation; sterilization; cardiac arrest; autopsy; negligence